2020
DOI: 10.1186/s12860-020-00329-3
|View full text |Cite
|
Sign up to set email alerts
|

An interaction of heart disease-associated proteins POPDC1/2 with XIRP1 in transverse tubules and intercalated discs

Abstract: Background Popeye domain-containing proteins 1 and 2 (POPDC1 and POPDC2) are transmembrane proteins involved in cyclic AMP-mediated signalling processes and are required for normal cardiac pacemaking and conduction. In order to identify novel protein interaction partners, POPDC1 and 2 proteins were attached to beads and compared by proteomic analysis with control beads in the pull-down of proteins from cultured human skeletal myotubes. Results Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 48 publications
(83 reference statements)
1
12
0
Order By: Relevance
“…Nevertheless, whether POPDC modulation of XIRP1 function is controlled via cAMP signaling is currently unknown. The same study that reported the XIRP1 interaction also demonstrated an interaction of POPDC1 with annexin A5 (ANXA5) [46]. Together with other annexin subunits, ANXA5 is recruited to the injured plasma membrane and forms a 2-dimensional array preventing an enlargement of the damaged area [128].…”
Section: Popdc Proteins and Plasma Membrane Compartmentsmentioning
confidence: 78%
See 4 more Smart Citations
“…Nevertheless, whether POPDC modulation of XIRP1 function is controlled via cAMP signaling is currently unknown. The same study that reported the XIRP1 interaction also demonstrated an interaction of POPDC1 with annexin A5 (ANXA5) [46]. Together with other annexin subunits, ANXA5 is recruited to the injured plasma membrane and forms a 2-dimensional array preventing an enlargement of the damaged area [128].…”
Section: Popdc Proteins and Plasma Membrane Compartmentsmentioning
confidence: 78%
“…Apart from some alterations in the structure of the sinus node cells, no structural defect has been described in POPDC mutants. However, POPDC proteins have a prominent expression in the intercalated disc (ID) and also interact with several proteins such as ZO1 [43] or XIRP1 [46], which suggests that they might possibly also have a role in controlling structure and function of the ID. From these concluding remarks, it becomes apparent that despite all the progress made and knowledge accumulated in the past 20 years, still more work on POPDC proteins needs to be conducted to better define their molecular functions in the heart and beyond.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations